Municipal zoning for movement of forest, fruit and agricultural germplasm to adapt to climate change - Manzanilla-Quijada, Gyorgy Eduardo; Sáenz-Romero, Cuauhtémoc; Gómez-Pineda, Erika; Lindig-Cisneros, Roberto (Ecosistemas y Recursos Agropecuarios, 2025)
Reforestation and crop establishment in a changing environment becomes increasingly complex and challenging in the context of climate change. The objective of this study was to define seed collection and guidelines for deciding seed transfer in seven municipalities within six Mexican states to guide reforestation and the establishment of agricultural-fruit crops of the Interinstitutional Program of Specialization in Food Sovereignty and Strategic Local Impact Management (PIES-AGILES, by its Spanish acronym) as a measure of adaptation to climate change. Maps were generated for seven municipalities located in the center and southeast of the country, to guide germplasm collection and movement under a reference climate (1961-1990), and for future climates: 2025 scenario RCP 8.5 for agricultural-fruit crops, and 2050 scenario RCP 4.5 for forest species. It is recommended to move seed sources from 3°C warmer and drier places to currently cooler and more humid planting sites, to compensate for the climate change.